RANCANG BANGUN SISTEM MONITORING PERKEBUNAN VERTIKAL TANAMAN BAYAM BRAZIL DENGAN SUMBER TENAGA LISTRIK DARI PANEL SURYA - Widyantoro, Salsa; Nurwati, Tri; Abidin, Zainul (Jurnal Mahasiswa TEUB, 2024)
Indonesia is a country with a large population and is ranked 4th in the world. However, the population in Indonesia is not evenly distributed and is mostly concentrated on the island of Java. This has a big impact on the agricultural sector, namely the reduction in agricultural land. Mitigation and adaptation ef orts are very important in dealing with this phenomenon, such as ef icient management of water resources, diversification of crops that are more drought resistant, and implementation of innovative agricultural technology. An innovative solution to overcome quality and quantity in the agricultural sector is to implement a vertical farming system. The application of vertical farming does not use soil as a planting medium and provides nutrients, but uses water flowed by a pump. Vertical Farming uses LED lights as additional light to support plant photosynthesis at night. However, using LED lights and pumps in a vertical farming system will require quite a lot of electricity. So it is necessary to addsolar panels to meet electricity needs. In this research, solar panels are connected to a battery to store electrical power. This vertical farming system prototype has been realised and is working well. Test results show that this system can be applied much better and more widely. Keywords— LED, Vertical Farming, solar panel